PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN (Studi pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia tahun 2017-2020) - Trigomer Nainggolan; Ickhsanto Wahyudi (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Investment is one of the activities that can provide benefits to several parties, such as for the progress of the company in running its business, even the development and growth of the economic sector in a country is also indicated by the number of investors who invest their funds or capital into securities companies in the capital market. Before investing in a company, investors will analyze companies that produce good stock returns, one of which is by analyzing the existing dividend policy in the company. This research was conducted to determine the effect of Profitability, Liquidity, Leverage, and Firm Size. The population using the Food and Beverage sub-sector companies for the 2017-2020 period amounted to 38 companies and the sample obtained was 10 companies using purposive sampling technique. The analysis in this study uses descriptive statistics, while hypothesis testing uses multiple linear regression. The results of this study indicate that there is a simultaneous influence between Profitability, Liquidity, Leverage, and Firm Size on dividend policy. Partially, only liquidity and firm size have a positive effect on dividend policy. Profitability and Leverage have no partial effect on dividend policy.